A phase 3 randomized, placebo-controlled study assessing the efficacy and safety of epoetin-α in anemic patients with low-risk MDS. Issue 12 (December 2018) - Fenaux, Pierre; Santini, Valeria; Spiriti, Maria; Giagounidis, Aristoteles; Schlag, Rudolf; Radinoff, Atanas; Gercheva-Kyuchukova, Liana; Anagnostopoulos, Achilles; Oliva, Esther; Symeonidis, Argiris; Berger, Mathilde; Götze, Katharina; et al.
Abstract Erythropoiesis-stimulating agents are first choice for treating anemia in low-risk MDS. This double-blind, placebo-controlled study assessed the efficacy and safety of epoetin-α in IPSS low- or intermediate-1 risk (i.e., low-risk) MDS patients with Hb ≤ 10.0 g/dL, with no or moderate RBC transfusion dependence (≤4 RBC units/8 weeks). Patients were randomized, 2:1, to receive epoetin-α 450 IU/kg/week or placebo for 24 weeks, followed by treatment extension in responders. The primary endpoint was erythroid response (ER) through Week 24. Dose adjustments were driven by weekly Hb-levels and included increases, and dose reductions/discontinuation if Hb > 12 g/dL. An independent Response Review Committee (RRC) blindly reviewed all responses, applying IWG-2006 criteria but also considering dose adjustments, drug interruptions and longer periods of observation. A total of 130 patients were randomized (85 to epoetin-α and 45 to placebo). The ER by IWG-2006 criteria was 31.8% for epoetin-α vs 4.4% for placebo (p  < 0.001); after RRC review, the ER was 45.9 vs 4.4% (p  < 0.001), respectively. Epoetin-α reduced RBC transfusions and increased the time-to-first-transfusion compared with placebo. Thus, epoetin-α significantly improved anemia outcomes in low-risk MDS. IWG-2006 criteria for ER may require amendments to better apply to clinical studies.